Penerapan Algoritma FP-Growth Untuk Mengetahui Pola Pada Data Transaksi Percetakan (Studi Kasus Java Printing Batujajar) - Sugianto, Castaka Agus; Sukmawati, Dini (LPPM STMIK AMIK BANDUNG, 2023)
Transaction data in the printing industry provides valuable insights into concurrently favored products by customers within a specific timeframe. Java Printing Batujajar has recorded printing transactions over the past 2 years. However, the lack of data management has led to disorganized raw material inventory, resulting in many unprocessed transaction records. The collected data consists of 704 printing transaction records from 2021 to 2022. Consequently, a solution is needed to identify patterns within this transaction data. This research aims to employ the association method with FP-Growth algorithm using the RapidMiner software. The research findings reveal an association between two products: